A comparative corpus-based analysis of lexical collocations used in EFL textbooks - Ahmad Molavi; Mansour Koosha; Hossein Hosseini (Universidad de La Sabana, 2014)
As collocations play an important role in second language learning, especially at intermediate-advanced levels, the present study not only seeks to examine distribution of Lexical collocations in three selected series of general English textbooks, Interchange Third Edition by (Jack C. Richards and Jonathan Hull, 2005), American Headway by (Liz and John Soars, 2003), American File by (Clive Oxenden and Christina Latham Koeing, 2008),through analyzing, face to face and telephone conversation scripts collected from intermediate and upper-intermediate level books of the aforementioned series, but also employs Open American National Corpus (OANC) available online and AntConc 3.2.1concordancer program to compare Lexical collocations from textbook to their real use by native-speakers. The findings of present research suggested that especial attention has been paid to specific types of lexical collocations noun + verb and adjective + noun while the frequency of collocations in series could not be affective on learners collocations learning and on the other hand comparing textbooks collocations to reference corpus (OANC) showed choice of collocations in these series did not have big refers to real use of language by native speakers.